The structural basis for an on-off switch controlling Gβγ-mediated inhibition of TRPM3 channels - Behrendt, Marc; Gruss, Fabian; Enzeroth, Raissa; Dembla, Sandeep; Zhao, Siyuan; Crassous, Pierre-Antoine; Mohr, Florian; Nys, Mieke; Louros, Nikolaos; Gallardo, Rodrigo; Zorzini, Valentina; Wagner, Doris; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2020)
TRPM3 channels play important roles in the detection of noxious heat and in inflammatory - thermal hyperalgesia. The activity of these ion channels i...
Gesehen am 17.04.2024